COVID-19 Impact Monitoring : Nigeria Round 6 - National Bureau of Statistics; World Bank (World Bank, Washington, DC, 2021)
The COVID-19 pandemic and its economic and social effects on households have created an urgent need for timely data to help monitor and mitigate the social and economic impacts of the crisis and protect the welfare of Nigerian society. To monitor how the COVID-19 pandemic is affecting the economy and people of Nigeria and to inform policy interventions and responses, the National Bureau of Statistics with technical support from the World Bank implemented the Nigeria COVID-19 National Longitudinal Phone Survey (COVID-19 NLPS). This brief presents findings from the sixth round of this survey which was conducted between October 9 and 24, 2020.